Positivism and Ibn Khaldun's thought: bridging objectivity and social dynamics - MR, Moh Irsyad Fahmi; Anam, Ahmad Muzakkil; Wiratmoko, Dheny; Yaacob, Norazlan Hadi; Alwiyah, Noor (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
This study critically examines two foundational approaches in social science: positivism and Ibn Khaldun's theoretical framework. Through comprehensive library research analyzing primary and secondary sources, we explore the ontological, epistemological, and axiological dimensions of both paradigms. Positivism, approaches social phenomena through rigid scientific methodologies, emphasizing empirical observation and quantitative measurement while pursuing objective, universal social laws. This perspective, while influential in modern social science development, often reduces complex social realities to measurable variables, neglecting subjective dimensions like values, culture, and historical contexts. In contrast, Ibn Khaldun's 14th-century framework, particularly his concept of asabiyyah (group solidarity), offers a more dynamic understanding of social phenomena by integrating empirical observation with philosophical reflection and historical context. This research demonstrates how Ibn Khaldun's approach acknowledges the multidimensional nature of social reality, including moral, spiritual, and cultural factors that remain influential in social development cycles. The comparative analysis reveals that while positivism provides methodological rigor, Ibn Khaldun's holistic perspective better captures the complexity and fluidity of social dynamics, making it particularly relevant for contemporary social analysis seeking to transcend mechanistic explanations. This study contributes to ongoing discourse about developing more integrative approaches in social science that balance empirical observation with contextual understanding.